Predictive accuracy of the shock index for severe postpartum hemorrhage in high‐income countries: A systematic review and meta‐analysis. Issue 8 (4th June 2022) - Makino, Yuto; Miyake, Kentaro; Okada, Asami; Ikeda, Yumie; Okada, Yohei
Abstract: Aim: The shock index has been suggested as a screening tool for predicting postpartum hemorrhage (PPH); however, there is little comprehensive evidence regarding its predictive accuracy. This systematic review and meta‐analysis aim to investigate the predictive accuracy of the shock index for severe PPH in high‐income countries. Methods: A comprehensive search was conducted on MEDLINE, Cochrane Central Register of Controlled Trials, and Web of Science (from inception to June 2021). Studies assessing the predictive performance of the shock index for PPH in high‐income countries were included. Two or more reviewers independently extracted the data and assessed the risk of bias and applicability concerns using the modified Quality Assessment of Diagnostic Accuracy Studies 2 tool. PPH requiring higher‐level care, such as blood transfusions, were considered as primary analyses. We described the hierarchical summary receiver‐operating characteristic curve for data synthesis. Results: Nine studies were included after the eligibility assessment. All studies were considered to either have a high risk of bias or high applicability concerns. The sensitivity of the four studies that defined severe PPH as PPH requiring blood transfusion ranged from 0.51 to 0.80, whereas their specificity ranged from 0.33 to 0.92. Conclusions: This review shows that the predictive performance of the shock index for severe PPH is inconsistent. Therefore, the evidence for using the shock index alone as a screening tool for PPH in high‐income countries is insufficient. Study registration: This review was prospectively registered with the University Hospital Medical Information Network Clinical Trials Registry (UMIN000044230).